A cost-minimization analysis of combination therapy in hypertension: fixed-dose vs extemporary combinations - Bellone, Marco; Sbarra, Pierluigi (Farmeconomia. Health Economics and Therapeutic Pathways, 2013)
BACKGROUND: Cardiovascular disease management and prevention represent the leading cost driver in Italian healthcare expenditure. In order to reach the target blood pressure, a large majority of patients require simultaneous administration of multiple antihypertensive agents.OBJECTIVE: To assess the economic impact of the use of fixed dose combinations of antihypertensive agents, compared to the extemporary combination of the same principles.METHODS: A cost minimization analysis was conducted to determine the pharmaceutical daily cost of five fixed dose combinations (olmesartan 20 mg + amlodipine 5 mg, perindopril 5 mg + amlodipine 5 mg, enalapril 20 mg + lercanidipine 10 mg, felodipine 5 mg + ramipril 5 mg, and delapril 30 mg + manidipine 10 mg) compared with extemporary combination of the same principles in the perspective of the Italian NHS. Daily acquisition costs are estimated based on current Italian prices and tariffs.RESULTS: In three cases the use of fixed‑dose combination instead of extemporary combination induces a lower daily cost. Fixed combination treatment with delapril 30 mg + manidipine 10 mg induces greater cost savings for the National Health System (95,47 €/pts/year), as compared to free drugs combination therapy.CONCLUSIONS: Compared with free drug combinations, fixed‑dose combinations of antihypertensive agents are associated with lower daily National Health Service acquisition costs.